Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/1747-0080.12039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a curriculum initiative designed to enhance the research training of dietetics graduates

Abstract: Aim To qualitatively evaluate a learning and teaching intervention for developing research and evaluation competencies, structured around the experience of having to conduct a significant research project. Methods A qualitative study utilising semi‐structured interviews among a sample of 25 recent graduates from Griffith University's Master of Nutrition and Dietetics Program. Interviews explored student motivations for doing the research major, the student's experience of the full‐time semester long research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
(17 reference statements)
1
19
0
Order By: Relevance
“…assessment) with participants being mostly from a single location (i.e. one university) . In the absence of empirical evidence exploring the perspectives of dietetics educators, it has been speculated that their challenges may include: sourcing suitable student placements; equipping graduates to practice internationally; having valid and consistent assessment tools; a more diverse and demanding student population; and teaching using relevant technology …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…assessment) with participants being mostly from a single location (i.e. one university) . In the absence of empirical evidence exploring the perspectives of dietetics educators, it has been speculated that their challenges may include: sourcing suitable student placements; equipping graduates to practice internationally; having valid and consistent assessment tools; a more diverse and demanding student population; and teaching using relevant technology …”
Section: Introductionmentioning
confidence: 99%
“…one university). [14][15][16][21][22][23][24] In the absence of empirical evidence exploring the perspectives of dietetics educators, it has been speculated that their challenges may include: sourcing suitable student placements; equipping graduates to practice internationally; having valid and consistent assessment tools; 25 a more diverse and demanding student population; 26 and teaching using relevant technology. 27 Recent research commissioned by national dietetics bodies in the USA, 26,28,29 the UK 30 and Canada 12,31 has attempted to inform dietetics workforce development and hypothesise on the future direction of the profession.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of research in dietetics workforce preparation found that students were the most frequently studied of all participant groups (33) . However, much of the research to date has taken a piecemeal approach and focused on single, selected aspects of student's educational experiences; for example, assessment (34) , simulation (35,36) , problembased learning (37) , interprofessional learning (38,39) , clinical activities (40)(41)(42) , volunteering (43) , research (44,45) and reflective practice (46,47) . Despite this body of evidence, the experiences of dietetics students regarding their education and preparation for the workforce have not been systematically synthesised.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to contributing to the theoretical underpinnings of the work by advancing knowledge, research can also enhance the knowledge and skills of academic advisors. Involvement in research in other practitioner‐oriented fields, such as dietetics, has been shown to help improve transferrable skills, such as critical thinking, time management, and self‐directed learning (Desbrow, Leveritt, Palmer, & Hughes, ). Involvement in research at any level has implications for professional and personal goals and growth.…”
Section: Practitioner Involvement In Researchmentioning
confidence: 99%